Magneto-plasmonic "switch" device for magnetic field detection - Bsawmaii, Laure; Giraud, Pascal; El Haber, Gerges; Halagacka, Lukas; Chatelon, Jean-Pierre; Jamon, Damien; Jourlin, Yves; Royer, François (Nanophotonics (Berlin, Germany), 2024)
This paper introduces a novel class of low-loss and cost-effective optical planar structures tailored for magnetic detection applications. These structures represent unconventional magneto-plasmonic devices specifically optimized for an 'optical switch' configuration. The structure consists of a 1D deep sinusoidal gold grating covered by a thin cobalt layer. In this unique arrangement, the excited plasmon induces a high-contrast switching phenomenon between the reflected free space intensity of specular (0th) and -1st diffracted orders, sensitive to any transverse magnetic fields applied to the cobalt layer. The use of these two distinct diffracted orders induces differential measurements, effectively mitigating common drift and perturbations. This innovative approach results in an enhanced detection sensitivity, showcasing the potential of these structures for advanced magnetic field sensing applications.
Keywords: magneto-optics; plasmonic; magnetic field sensors